DEVELOPING A WEBSITE-BASED COMPANY PROFILE USING WORDPRESS CMS AS A PROMOTONAL MEDIUM AT CV PIJAR PENDAR PUSTAKA IN MALANG CITY - Riskiyah, Bidayatul; Utomo, Heru; Wardani, Tri Istining (Transpublika Publisher, 2024)
The appropriate and targeted promotional media can help a company grow and increase its reach to customers. After observing the promotional activities at CV Pijar Pendar Pustaka company, it was found that they were only using word of mouth and Instagram. This limited the effectiveness of their promotional activities. Therefore, this research aims to develop an additional promotional medium in the form of a company profile website using WordPress CMS. This website will provide real-time and comprehensive information to customers. The research methodology used in the present study was action research. It involved observations, interviews, documentation, and distributing questionnaires, as the data collection method. The EPIC model was employed to measure the website's effectiveness as a promotional medium. The results indicated that the company profile website was considered as a highly effective promotional medium. This was supported by the scores of 4.45 for the Empathy dimension, 4.37 for the Persuasion dimension, 4.27 for the Impact dimension, and 4.42 for the Communication dimension, resulting in an overall EPIC Rate of 4.37. It can be concluded that the company profile website is suitable for use as a promotional medium for CV Pijar Pendar Pustaka. The website enables optimal conveyance of service information and provides wide promotional reach accessible from anywhere and at any time.